Fertigungsqualität beim 3D-Laserstrahlschweißen von Blechformteilen - Schultz, Markus (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1997)
Within this thesis the quality of 3D laser welds along contours with small radii at shaped sheet metal parts has been investigated and documented by significant examples. These results were applied to establish design guidelines for laser welding of shaped sheet metal parts. The three most relevant joint geometries for laser welding of sheets in car body production have been investigated during the experiments: Butt weld, lap weld and lap fillet weld. To evaluate the weld quality of lap and lap fillet welds quality levels for imperfections for these joint geometries had to be defined. Shaped sheet metal workpieces - simple, bended parts and complicated deep drawn car body parts - were welded by the application of different processing strategies - some of them already known and others developed during the investigations. The quality of the welding results was evaluated using the above mentioned quality levels. Good weld quality at all welded parts even at complicated parts like small radii could be achieved by the application of suitable processing strategies. The experiments were performed using a 5-axis gantry machine with a 2.2kW CO2-Laser and a 6-axis industrial robot with a 1kW Nd:YAG-Lase